Healthcare professionals: spirituality and meaning of life during the COVID-19 pandemic (Research, Society and Development, 2023)
The coronavirus disease (COVID-19) has brought great challenges to health care professionals. Spirituality and meaning of life are themes discussed by several authors as important to face adverse life situations. This study aimed to analyze how meaning of life and spirituality offer support to health professionals, and their practices, during the pandemic. A study of mixed nature was conducted, combining quantitative and qualitative research. Quantitative data were obtained through the Sociodemographic Questionnaire and the Meaning of Life Questionnaire (QSV). Sixty-two participants were included in the study by the inclusion criteria. Qualitative data were obtained through a semi-structured interview with 05 participants. The information was collected online. The quantitative data analysis was done by descriptive statistics, while the qualitative data analysis was done by Minayo's thematic content analysis. The results indicated that health professionals demonstrate spirituality and the meaning of life as coping strategies to deal with the stressful situations of the pandemic. The quantitative data pointed to a prevalence of the presence of the meaning of life in detriment of the search for meaning, which was manifested through the speeches of the participants, who stated that having clarity about the meaning of life helped them to face a delicate moment such as the pandemic of COVID-19. It is understood, therefore, the importance and relevance that these themes present in the current scenario.